ИЗУЧЕНИЕ ЗНАЧИМОСТИ РАЗРАБОТКИ МОДЕЛИ ИСКУССТВЕННОГО ИНТЕЛЛЕКТА ДЛЯ РАСПОЗНАВАНИЯ КАРАКАЛПАКСКОГО ЯЗЫКА ЖЕСТОВ - Толыбаева, Г.Н. (SCIENCE and SOCIETY, 2024)
The article examines the significance of developing an artificial intelligence model for the recognition of the Karakalpak sign language. Technological solutions for gesture recognition play an important role in improving the quality of life and social integration of deaf people.
Keywords: artificial intelligence; Karakalpak sign language; CNN; RNN; gesture recognition; minor sign languages; inclusive education and training